Autoantibody profile and clinical patterns in 619 Italian patients with cutaneous lupus erythematosus. (12th July 2018) - Verdelli, A.; Coi, A.; Marzano, A.V.; Antiga, E.; Cozzani, E.; Quaglino, P.; La Placa, M.; Benucci, M.; De Simone, C.; Papini, M.; Parodi, A.; Bianchi, F.; et al.
Abstract: Background: Anti‐nuclear antibodies (ANA), anti‐extractable nuclear antigens (ENA) and anti‐dsDNA antibodies are often associated with cutaneous lupus erythematosus (CLE), with variable frequency depending on skin subtype. However, specific data based on large case‐series on the pathogenetic, diagnostic and prognostic meaning of such autoantibodies are still lacking. Objective: To characterize the correlations between CLE subtypes as well as LE‐non‐specific skin lesions and their autoantibody pattern. Methods: Epidemiological, clinical and immunopathological data of 619 Italian patients with CLE and LE‐non‐specific skin lesions were analysed. Differences in age, sex, clinical features and autoantibody profile were evaluated in each LE subgroup. Results: Anti‐nuclear antibodies ( P < 0.0001), anti‐dsDNA ( P < 0.0001), ENA ( P = 0.001), anti‐Sm ( P = 0.001), anti‐RNP ( P = 0.004) and anti‐histone ( P = 0.005) antibodies were associated with SLE. A strong association between ANA ( P < 0.0001) and anti‐dsDNA ( P < 0.0001) and female gender was also found: positive ANA and positive anti‐dsDNA had a higher prevalence among females. Chronic CLE resulted to be negatively associated with ENA (OR = 0.51, P < 0.0001), anti‐Ro/SSA (OR = 0.49, P < 0.0001) and anti‐dsDNA (OR = 0.37, P < 0.0001). Intermittent CLE resulted to be negatively associated with ENA (OR = 0.50, P = 0.007) and ANA (OR = 0.61, P = 0.025). Subacute CLE resulted to be associated with ENA (OR = 5.19, P < 0.0001), anti‐Ro/SSA (OR = 3.83, P < 0.0001), anti‐Smith (OR = 2.95, P = 0.004) and anti‐RNP (OR = 3.18, P = 0.007). Acute CLE resulted to be strongly associated with anti‐dsDNA (OR = 6.0, P < 0.0001) and ANA (OR = 18.1, P < 0.0001). LE‐non‐specific skin lesions resulted to be significantly associated with systemic involvement. Livedo reticularis was significantly associated with ENA ( P = 0.007) and anti‐Ro/SSA ( P = 0.036). Palpable purpura and periungual telangiectasia were significantly associated with ANA. Conclusion: According to our findings, some well‐known associations between CLE subtypes and autoantibody profile were confirmed; moreover, specific association between autoantibodies and LE‐non‐specific skin lesions was highlighted. A strict association between anti‐ENA and anti‐Ro/SSA antibodies and livedo reticularis, ANA and palpable purpura, and ANA and periungual telangiectasia was evidenced.